EYE-GG: Prototipo plug in y aplicativo orientado a la salud visual de los gamers (2023)
The objective of this degree project is to propose an outreach strategy aimed at promoting information through the prototyping of a plug-in and a mobile application; in order to promote healthy practices and prevent possible visual conditions in this population, which are evidenced as a result of excessive exposure to screens for 5 or more hours of consecutive gaming per day.